GERICHTSVERFAHREN PER VIDEOKONFERENZ ALS EINE NEUE HERAUSFORDERUNG FÜR GERICHTSDOLMETSCHER - Łomzik, Magdalena (Comparative Legilinguistics, 2022)
The Covid-19 pandemic has significantly increased the meaning of videoconferencing in a professional setting. Furthermore, there has been an increase in the number of court hearings held via videoconference, although the advantages of this form of trial are still being questioned. Videoconferencing in court has also become a new challenge for court interpreters. Unfortunately, there are no current studies of Polish associations of translators which would provide a comprehensive presentation of issues related to translation in court by means of remote translation devices. However, the positions of the German associations of interpreters and translators contain an extensive mention of the advantages and disadvantages of this form of translation. The purpose of this article is to demonstrate the possible issues related to court interpreting by means of videoconferencing based on the expertise of translators from Germany and Austria and of the author.